Pengaruh Model PBL Dan Evaluasi Berbasis Hots Terhadap Hasil Belajar Bilangan Bulat Kelas VI SD Negeri Desa Dodap - Rorimpandey, Widdy; Lumintang, Pricilian; Tuerah, Philotheus (Jurnal Elementaria Edukasia, 2023)
This study aims to determine the effect of the model problem-based learning and HOTS-based evaluation of mathematics learning outcomes for grade VI students at Elementary School in Dodap Village. The population in this study amounted to 36 students. This study used a quantitative approach research design. The analysis used multiple regression analysis to see the effect of the model problem-based learning and hots-based evaluation of mathematics learning outcomes in integer material. The research results obtained (1) model problem-based learning effect on the results of learning mathematics this is evidenced by the value themselves 0.00 <0.05 which means there is an influence. (2) HOTS-based evaluation has an effect on mathematics learning outcomes, this is evidenced by grades themselves namely 0.00 <0.05 which means there is an influence of (3) model problem-based learning and HOTS-based evaluations simultaneously affect the results of learning mathematics, this is evidenced by gradesR Square is 0.669 or 66.9%. This means that the ability of the learning model problem-based learning and the results of the HOTS evaluation are able to explain the learning outcomes of 66.9%, the remaining 33.1% is explained by other variables not explained in the study. The same thing with research conducted by (Agustin et al., 2019) the PBL model can improve learning outcomes because of problem solving activities. (Sari & Rakhmawati, 2023) HOTS-based evaluation can improve mathematics learning outcomes if continuously trained and studied. (Mustofa, 2022) model problem-based learning and HOTS-based evaluation can simultaneously improve mathematics learning outcomes.